2020
DOI: 10.1073/pnas.2016539117
|View full text |Cite
|
Sign up to set email alerts
|

LRRC8 family proteins within lysosomes regulate cellular osmoregulation and enhance cell survival to multiple physiological stresses

Abstract: LRRC8 family proteins on the plasma membrane play a critical role in cellular osmoregulation by forming volume-regulated anion channels (VRACs) necessary to prevent necrotic cell death. We demonstrate that intracellular LRRC8 proteins acting within lysosomes also play an essential role in cellular osmoregulation. LRRC8 proteins on lysosome membranes generate large lysosomal volume-regulated anion channel (Lyso-VRAC) currents in response to low cytoplasmic ionic strength conditions. When a double-leucine L706L7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 52 publications
1
59
0
Order By: Relevance
“…A major outstanding question in the field is how endosomes sense their luminal contents to direct traffic. As previously alluded to, cation channels (e.g., TRPML), PIKfyve, and VRAC/LRRC8 are all responsive to endomembrane tension and/or osmotic stress, suggesting that there are numerous feedback mechanisms for the cell to calibrate ion transport to the tension experienced at organelles (Bonangelino et al, 2002 ; Chen et al, 2020 ; Li et al, 2020 ). Tension on the endomembrane may impact lipid packing or spacing of lipid headgroups and could conceivably recruit or activate signaling complexes that sense these events.…”
Section: Mainmentioning
confidence: 95%
See 1 more Smart Citation
“…A major outstanding question in the field is how endosomes sense their luminal contents to direct traffic. As previously alluded to, cation channels (e.g., TRPML), PIKfyve, and VRAC/LRRC8 are all responsive to endomembrane tension and/or osmotic stress, suggesting that there are numerous feedback mechanisms for the cell to calibrate ion transport to the tension experienced at organelles (Bonangelino et al, 2002 ; Chen et al, 2020 ; Li et al, 2020 ). Tension on the endomembrane may impact lipid packing or spacing of lipid headgroups and could conceivably recruit or activate signaling complexes that sense these events.…”
Section: Mainmentioning
confidence: 95%
“…Whether this effect is directly caused by the loss of VRAC activity from endosomes remains to be formally tested. Should VRAC function along the endocytic pathway (Li et al, 2020 ), its flux of Cl − and that of several organic anions (Jentsch, 2016 ; Kasuya et al, 2018 ), could yield pleiotropic control over trafficking.…”
Section: Mainmentioning
confidence: 99%
“…Furthermore, osmotic volume changes promote membrane trafficking events (Freeman and Grinstein, 2018 ; Freeman et al, 2020 ; Saric and Freeman, 2020 ) and the number of known osmo-sensitive cation channels of endosomes and lysosomes is growing (Chen et al, 2020a , b ). Recently, the LRRC8-formed volume-regulated anion channel (VRAC) has been reported to localize to lysosomes where it contributed to cellular osmoreglation (Li et al, 2020 ). This plasma membrane channel, which is involved in multiple physiological processes, does not only mediate cell volume regulatory ion transport (Chen et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…By whatever way, as upon hypertonic cell shrinkage also vesicles rapidly shrink, it can be deduced that the intrinsic water permeability is sufficiently high to allow for timely vesicular volume changes during resolution of macropinosomes ( Freeman and Grinstein, 2018 ). Using fluorescence enhancement of Lucifer yellow dextran by deuterated water, Li et al (2020) have recently demonstrated that lysosomes rapidly swell in response to a hypoosmotic challenge, indicating that there is substantial water influx into the lumen of lysosomes soon after water penetration across the PM, again indicating that the intrinsic water permeability of these organelles is high.…”
Section: Water Ions and Their Channels And Transporters In Pinocytosismentioning
confidence: 99%
“…The Cl – channels and transporters expressed in intracellular organelles include the ClC family members ClC-3 through 7, chloride intracellular channels (CLICs), CFTR, AQP6, transmembrane proteins (TMEM)16C–G/anoctamin (ANO) 3–7, bestrophin-1, Golgi pH regulator (GPHR) (reviewed in Stauber et al, 2012 ; Stauber and Jentsch, 2013 ), Tweety homolog 1 (Ttyh1) proteins ( Wiernasz et al, 2014 ), LRRC8 ( Li et al, 2020 ), and TMEM206 ( Osei-Owusu et al, 2021 ).…”
Section: Water Ions and Their Channels And Transporters In Pinocytosismentioning
confidence: 99%